About the cover image - Editors, The (feminists@law, 2014)
This issue features a piece of artwork by Hannah Tiernan. Hannah graduated in 2013 from the National College of Art and Design, Dublin and is now studying photography at Griffith College Dublin. She works mainly in sculpture, installation and photography. She has exhibited her work on a number of occasions in Dublin, including a solo show at the Hendrons Collider gallery space. The featured piece is 'Amber Topography'. This image is a detail from a wax study on skin. It was taken from a clay press mould of overlapping feathers. Using light to illuminate the wax, the resulting image is somewhat reminiscent of geographical shipping charts. For more of Hannah's work please visit her Facebook page at https://www.facebook.com/HannahTiernanArtist?ref=stream.